Increased grp78 transcription is correlated to reduced tlr4 transcription in patients surviving sepsis. (6th August 2019) - Stan, R. C.; Pinto Bonin, C.; Porto, R.; Soriano, F. G.; de Camargo, M. M.
Summary: Regulated transcriptional readthrough during stress maintains genome structure and ensures access to genes that are necessary for cellular recovery. A broad number of genes, including of the bacterial sensor Toll‐like receptor 4 (TLR‐4), are markedly transcribed on initiating the systemic inflammatory response. Here we study the transcriptional patterns of tlr4 and of its modulator grp78 during human sepsis, and establish their correlations with the outcome of patients. We measured the daily tlr4 and grp78 RNA expression levels in peripheral blood of septic patients, immediately after admission to intensive care, and modeled these RNA values with a sine damping function. We obtained negative correlations between the transcription of tlr4 and grp78 RNA in the survivor group. In contrast, such relation is lost in the deceased patients. Loss of transcriptional homeostasis predicted by our model within the initial 4 days of hospitalization was confirmed by death of those patients up to 28 days later. Abstract : Experimental data and fitted curves of averaged mRNA time‐courses of two sepsis markers ( tlr4 and grp78 ) in patients surviving sepsis, highlighting the inverse correlation in their expression patterns.